2022
DOI: 10.3389/fpls.2022.973591
|View full text |Cite
|
Sign up to set email alerts
|

AabHLH112, a bHLH transcription factor, positively regulates sesquiterpenes biosynthesis in Artemisia annua

Abstract: The bHLH transcription factors play important roles in the regulation of plant growth, development, and secondary metabolism. β-Caryophyllene, epi-cedrol, and β-farnesene, three kinds of sesquiterpenes mainly found in plants, are widely used as spice in the food industry and biological pesticides in agricultural production. Furthermore, they also have a significant value in the pharmaceutical industry. However, there is currently a lack of knowledge on the function of bHLH family TFs in β-caryophyllene, epi-ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…α-Farnesene biosynthesis was mainly affected by the AFS genes in plant, and its expression was generally synchronous with its product (Du et al, 2022; Xiang et al, 2022). In this study, a DdeAFS gene was identified, which showed a significantly positive correlation with α-farnesene content, inferring that it was a key enzyme gene in α-farnesene biosynthesis in D. delavayi fruit.…”
Section: Discussionmentioning
confidence: 99%
“…α-Farnesene biosynthesis was mainly affected by the AFS genes in plant, and its expression was generally synchronous with its product (Du et al, 2022; Xiang et al, 2022). In this study, a DdeAFS gene was identified, which showed a significantly positive correlation with α-farnesene content, inferring that it was a key enzyme gene in α-farnesene biosynthesis in D. delavayi fruit.…”
Section: Discussionmentioning
confidence: 99%
“…AabHLH112 acts as an indirect positive regulator of artemisinin via binding to the AaERF1 promoter [ 113 ]. A recent study showed AabHLH112 also played key roles in promoting the biosynthesis of other sesquiterpenes such as β-caryophyllene, epi-cedrol, and β-farnesene [ 78 ]. In addition to those positive regulators, AabHLH2 and AabHLH3, which belong to MYC-type bHLH TFs, were recently identified as negative regulators of artemisinin synthesis [ 79 ].…”
Section: Transcriptional Regulatory Networkmentioning
confidence: 99%
“…BIGPETALp, another gene encoding bHLH TF, regulates petal growth by interfering in postmitotic cell expansion [31]. Recent research has identified AabHLH112 as a positive regulator of sesquiterpenes biosynthesis (β-caryophyllene, epi-cedrol, and β-farnesene) in Artemisia annua L. (Asteraceae) [32]. In Solanum lycopersicum L. (Solanaceae), knockdown of SlMYC1 resulted in the reduction in monoterpene content in leaf and stem trichome and sesquiterpenes (β-caryophyllene and α-humulene) in leaf trichome, while the content of β-caryophyllene and α-humulene increased in stem trichome, indicating differential regulation by SlMYC1 [33].…”
Section: Introductionmentioning
confidence: 99%